Ideological and Artistic Originality of French Children’s Literature of 19th Century: E. d’Hervilly “Adventures of a Prehistoric Boy” - T. V. Nuzhnaya (Научный диалог)
The article deals with the theme of the formation of children’s literature in the 19th century in France. The relevance of the study is due to the constant interest of both researchers and a wide range of readers in children’s literature as a source of reflection of the socio-cultural characteristics of a particular society. The story of the little-known French romantic writer Ernest d’Hervilli “The Adventures of a Prehistoric Boy”, which has not previously become the object of a special analysis, is examined. The author of the article reveals a pronounced ideological originality of the story, its compositional and artistic features. The nusualness of the reference of the French writer to the late Paleolithic era is emphasized. The author of the article believes that the main character is one of the first examples of a primitive romantic hero. It is argued that thanks to the story of Ernest d’Hervilli in the literature of the 19th century, the theme of the prehistoric past of human, interest in primitive society and the psychology of the maturation of a teenager in a certain period of history appears. It is shown that at the compositional level, taking into account the adventurous register, the author draws attention to the little-known pages of the history of mankind and, thanks to various means of verbal expression, creates a realistic picture of the life, nature and life of the Cro-Magnons.